Training On The Application Of Mendeley Software In Writing Scientific Works For Elementary School Teachers - Supriatna, Eka; Fitriyanto, A. Alvian; Pertiwi, a.n. Triani Patra; Efrina, Gusnita; Sutarto, Sutarto; Rijal, Syamsu (Journal Of Human And Education (JAHE), 2023)
Mendeley is applied to create citations and bibliography in scientific works. Mendeley will really help students in completing assignments. Apart from the process being easy and saving time, using Mendeley can also prevent plagiarism. To overcome the problem of teachers not being able to create well-organized citations and bibliography, Mendeley Software training was carried out to improve the quality of scientific work. The approach used is in the form of training that is more about direct practice in the scientific work that is being prepared. This service activity is carried out offline according to the planned schedule. The number of participants who took part in this activity was 20 teachers who delivered material using the Mendeley application to help make references easily. Of the 20 students, 12 were new to the Mendeley application, and 3 had installed the application but did not understand how to use it and 5 had installed it and understood how to use it. From activities carried out via Zoom, teachers can already apply Mendeley. Teachers are able to make references easily using the Mendeley application. They are able to enter manually and enter PDF references for the articles used.